Comparison of Some Semi-parametric Methods in Partial Linear Single-Index Model - Ahmed, Huda Yahya; Hmood, Munaf Yousif (Journal of Economics and Administrative Sciences, 2021)
The research dealt with a comparative study between some semi-parametric estimation methods to the Partial linear Single Index Model using simulation. There are two approaches to model estimation two-stage procedure and MADE to estimate this model. Simulations were used to study the finite sample performance of estimating methods based on different Single Index models, error variances, and different sample sizes , and the mean average squared errors were used as a comparison criterion between the methods were used. The results showed a preference for the two-stage procedure depending on all the cases that were used